Fungsi Spiritual dari Ritual Hole dalam Pertanian di Masyarakat Adat Liae Suku Jingtiu - Anderias Rondo; Bambang Hudayana (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The hole ritual is a local wisdom of the Jingtiu tribe that has a strong spiritual value in regulating the order of life up to the agricultural pattern of the local community. This study aims to describe the spiritual function of the hole ritual in agriculture in the Liae indigenous people of the Jingtiu tribe in the Liae Sub-District, Sabu-Raijua District, East Nusa Tenggara. In addition, this research also tries to explain the meaning and philosophy in the hole ritual which will strengthen the description of the function of the ritual itself. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and literature study. The results showed that the hole ritual has a spiritual function that can affect agricultural output. Obedience to rituals can bring blessings and keep away any harm that threatens agricultural products. The spiritual function creates a harmonious relationship between the human creator and the universe.